Juvenile Criminal Law Enforcement in Gangster Cases at Sidoarjo Police: Penegakan Hukum Pidana Anak dalam Kasus Gangster di Kepolisian Sidoarjo - Rachman, Dhea Amanda Aulia; Rosnawati, Emy (Indonesian Journal of Law and Economics Review, 2025)
Background: Juvenile crime cases involving gangster groups have become a growing social problem that requires special legal handling. Specific Background: This study focuses on the legal process of handling children involved in gangster-related crimes at the Sidoarjo Police Department. Knowledge Gap: Previous studies have rarely discussed the practical application of the juvenile justice system in regional law enforcement. Aim: To analyze the implementation of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System in dealing with child offenders. Results: The findings show that the Sidoarjo Police prioritize a restorative justice approach and diversion, balancing between justice enforcement and child protection. Novelty: This study presents a comprehensive overview of law enforcement efforts combined with social rehabilitation principles. Implication: The research implies that sustainable coordination among law enforcement officers, families, and social institutions is crucial in reducing juvenile crime recurrence. Highlights:• Juvenile crime handling through restorative justice• Implementation of Law No. 11/2012 at Sidoarjo Police• Legal protection for children in gangster cases Keywords: Juvenile Justice, Gangster Crime, Law Enforcement, Child Protection, Restorative Justice